The Operating Performance of Firms Conducting Seasoned Equity Offerings - Loughran, Tim; Ritter, Jay R. (Journal of Finance, 1997)
Recent studies have documented that firms conducting seasoned equity offerings have inordinately low stock returns during the five years after the offering, following a sharp run-up in the year prior to the offering. This article documents that the operating performance of issuing firms shows substantial improvement prior to the offering, but then deteriorates. The multiples at the time of the offering, however, do not reflect an expectation of deteriorating performance. Issuing firms are disproportionately high-growth firms, but issuers have much lower subsequent stock returns than nonissuers with the same growth rate.